Position of Sanskrit language and Sanskrit Education in Nepal - Adhikari, Rishiram (Haimaprabha, 2025)
Sanskrit is one of the oldest languages of the world. It is known as the language of gods and goddesses. In Nepal, the Sanskrit language has been utilized in educational practices since the time of following Vedic tradition. This study examines the current status of the Sanskrit language and its educational framework in Nepal today. The study seeks the answers of the question why does controversy create in Sanskrit language and education in Nepal. The study followed the qualitative research design and interpretative paradigm. Data from both primary and secondary sources were used in this study. Books, articles, reports were used as secondary source of data. Library and internet research method were used to gather the secondary data. Primary data were gathered through in-depth interview. Three scholars were selected from Kathmandu for in- depth study by using convenient sampling method. Conclusion of the study is based on both primary and secondary source of the data. Government policies controversy on Sanskrit education and language, attitudes of people play role to bring new crisis on Sanskrit language and Sanskrit education in Nepal.